MENINGKATAN KEMAMPUAN LITERASI MELALUI STRATEGI LICALIDO (LIHAT BACA TULIS DONGENG) DI SDN JATIRAHAYU VIII - Dedeh Kurniati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This best practice aims to provide an overview of the activities for implementing literacy skills through the LICALIDO strategy (See Read Write Tales), and describe the achievements after improving literacy skills through this LICALIDO strategy at SD Negeri Jatirahayu VIII. The result of this best practice is a significant increase in literacy skills in terms of reading comprehension, writing short stories or essays, and telling stories about the essays they have made. So, in the end the students can achieve achievements in the field of literacy.